2020
DOI: 10.1111/cts.12882
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Drug‐Induced Long QT Syndrome for Some COVID‐19 Repurposed Drugs

Abstract: The risk‐benefit ratio associated with the use of repurposed drugs to treat severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2)‐related infectious coronavirus disease 2019 (COVID‐19) is complicated because benefits are awaited, not proven. A thorough literature search was conducted to source information on the pharmacological properties of 5 drugs and 1 combination (azithromycin, chloroquine, favipiravir, hydroxychloroquine, remdesivir, and lopinavir/ritonavir) repurposed to treat COVID‐19. A risk ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 39 publications
0
31
2
2
Order By: Relevance
“…[ 14 ] In addition, pharmacovigilance investigations are still necessary for cardiac risk with remdesivir as a previous study reported the potential block of hERG (human ether‐a‐go‐go gene) and prolongation of cardiac repolarization with remdesivir. [ 15 ] Post hoc analyses of trials and additional observational studies are needed to corroborate our findings. Given the increased use of remdesivir and recent FDA recommendations, physicians should be aware of this cardiac safety signal.…”
Section: Discussionmentioning
confidence: 59%
“…[ 14 ] In addition, pharmacovigilance investigations are still necessary for cardiac risk with remdesivir as a previous study reported the potential block of hERG (human ether‐a‐go‐go gene) and prolongation of cardiac repolarization with remdesivir. [ 15 ] Post hoc analyses of trials and additional observational studies are needed to corroborate our findings. Given the increased use of remdesivir and recent FDA recommendations, physicians should be aware of this cardiac safety signal.…”
Section: Discussionmentioning
confidence: 59%
“…This may be particularly important for remdesivir and favipiravir, given their potential as COVID-19 treatments. Indeed, the present study usefully complements a recent independent investigation that has used a combination of predictive indices for drug-induced LQTS (though not structural modeling as conducted here) to evaluate risks with potential COVID-19 treatments, on the basis of which it has recommended close monitoring of QT/QT c intervals in patients receiving both drugs (67). On the basis of our observations, we suggest that a direct in vitro experimental comparison would be informative of I hERG inhibitory potency between remdesivir, atazanavir, lopinavir, and ritonavir and favipiravir under a standardized set of conditions; this would aid further evaluation of likely I hERG safety margin.…”
Section: Limitations and Conclusionmentioning
confidence: 83%
“…Repurposed drugs used in COVID-19 treatment cause QT prolongation by blocking the voltage-gated ion channel that mediates the rapid component of the delayed rectifier potassium current, IKr, resulting in lengthening of the ventricular action potential. 24 A timely early Afterdepolarisation, in the presence of a prolonged QT interval, may result in TdP. This risk increases in the presence of concomitant use of QT prolonging agents, loop diuretic, female gender, elderly people, structural heart disease, heart failure, myocardial infarction, electrolyte disturbances, bradycardia, renal disease and hepatic disease.…”
Section: Discussionmentioning
confidence: 99%